2010
DOI: 10.1074/jbc.m110.116749
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of a Novel Cdc42 Binding Module of Bem1 and Its Interaction with Ste20 and Cdc42

Abstract: Bem1 is a scaffold protein essential for the establishment of cell polarity in Saccharomyces cerevisiae. This work reports the solution structure of a Cdc42 binding module of Bem1 comprising the second SH3 domain (SH3b) and its C-terminal flanking region termed Cdc42 interacting (CI). First, the structure of Bem1 SH3b-CI was determined by NMR spectroscopy, which shows that Bem1 SH3b-CI is a structurally and functionally related domain that binds Cdc42. Next, the solution structure of Bem1 SH3b-CI in complex wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Adaptor protein Bem1 provides an example of where the binding site of the proline-rich region extends to the Cterminus and, in addition to the SH3 domain, utilizes the CI region (Takaku et al 2010). Interestingly, the tyrosine kinase, spectrin and myosin SH3 show similar structures and mode of peptide binding, with the formation of several hydrogen bonds and the interactions exhibiting a mainly hydrophobic character (Fig.…”
Section: Specificity Of Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…Adaptor protein Bem1 provides an example of where the binding site of the proline-rich region extends to the Cterminus and, in addition to the SH3 domain, utilizes the CI region (Takaku et al 2010). Interestingly, the tyrosine kinase, spectrin and myosin SH3 show similar structures and mode of peptide binding, with the formation of several hydrogen bonds and the interactions exhibiting a mainly hydrophobic character (Fig.…”
Section: Specificity Of Bindingmentioning
confidence: 99%
“…Although many SH3 domains are soluble, some are difficult to isolate. For example, the Bem1 SH3 domain is insoluble and forms a functional module only together with its C-terminal CI region (Takaku et al 2010). The amino-terminal β-strand can be aggregation-prone, and the absence of the carboxyl terminus leads to fibril formation (Neudecker et al 2012).…”
Section: Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Second, how do these domains also exhibit distinctive specificities toward other peptides? To answer these questions, we have solved the structure of the NbpSH3 domain in complex with the Ste20 peptide and compared it with the previously determined structure of the BemSH3b-Ste20 complex (21). Using a combination of structural analysis and in vitro assays involving mutant domains and peptides, we have dissected the binding mechanisms of these two SH3 domains.…”
mentioning
confidence: 99%
“…The BemSH3b domain binds to the PXXP motifs within Ste20p and Cla4p kinases and also binds Cdc42p itself in a PXXP-independent manner (16,17,19,20). The interaction between the BemSH3b domain and Cdc42p involves a unique C-terminal extension (Cdc42-interacting (CI) subdomain) in the BemSH3b domain, which is also required for the folding of the whole domain (19,21). The structure of the BemSH3b domain solved in complex with a peptide from Ste20p showed that the CI subdomain is intimately packed against the SH3 domain and is involved in the interaction with the peptide (21).…”
mentioning
confidence: 99%